(untitled) (Damu Journal of Sport Sciences, 2025)
The study aimed to identify the effect of interval training on the development of some functional variables in tennis players. The researcher used an experimental approach appropriate to the nature of the existing problem and used a sample of (16) players using a deliberate approach. Additionally, he used several methods, tools, and tests, the most important of which was the use of high-intensity interval training. After conducting the tests and obtaining the results, they were statistically processed. In light of this, the researcher concluded that systolic and diastolic blood pressure are significantly affected by the use of the exercises prepared by the researcher. The researcher recommends adopting the high-intensity interval training method when training tennis players